"That was our afterparty": a qualitative study of mobile, venue-based PrEP for MSM - Grace Chamberlin; Mairead Day Lopes; Surabhi Iyer; Christina Psaros; Ingrid V. Bassett; Susana Medeiros; Catherine O'Connor; Kevin L. Ard (BMC, 2023)
Abstract Background HIV preexposure prophylaxis (PrEP) uptake among men who have sex with men (MSM), a group disproportionately impacted by HIV, is not commensurate with need. Settings which reduce or remove barriers to accessing care are promising venues to support PrEP uptake. PrEP provision at mobile clinics represents a novel strategy to increase PrEP access; however, the acceptability and feasibility of this approach have not been well studied. Methods Our objective was to understand patient and staff experiences of a mobile clinic van offering PrEP and sexual health services in Boston, Massachusetts, USA. We interviewed mobile unit users and conducted focus groups with mobile unit staff and users. Data were organized using Dedoose software, and content analysis was used to identify themes of access, community, and stigma. Results Nineteen individuals (16 patients and 3 staff members) participated in interviews (N = 13) or focus groups (N = 6). All patients identified as MSM, 63% were Hispanic or Latino, and 21% of patient interviews were conducted in Spanish. Logistical and psychological convenience facilitated service use, while the community-oriented environment improved satisfaction with care. Overall, participants supported expansion of mobile unit services and recommended changes to improve access to longitudinal care. However, some barriers to PrEP persisted, including low HIV risk perception and stigma about sexual behavior. Conclusions Mobile units can promote sexual health and PrEP uptake, particularly for populations facing social and logistical barriers to care in traditional settings.